INOVASI PELAYANAN PUBLIK DIGITAL SIPP: ANALISIS PROSES, MAKNA, DAN KEBERLANJUTAN DALAM KERANGKA E-GOVERNANCE KABUPATEN PASAMAN BARAT - Finan Sari Lubis; Aldri Frinaldi; Roberia (Merwin Publisher, 2026)
Digital transformation in public services is increasingly pressing to improve government efficiency and accountability (Yusifov & Gurbanov, 2024). This study aims to examine how the digital public service innovation SiPP (Training and Unemployment Data Information System) in West Pasaman Regency functions in three dimensions: Process, Meaning, and Sustainability. Using a qualitative case study design, data were collected through a triangulation of methods: in-depth interviews with Department employees and Village/Jorong Wali operators, direct observation of operational processes, and analysis of official documentation (SOPs and system logs). Key findings indicate that SiPP is able to reduce data search and compilation time from a full day to less than 10 minutes and achieves a very high level of user acceptance (93.3% of respondents reported no problems), indicating that the system is accepted and functional in daily bureaucratic practice. On the sustainability front, although the system supports real-time data updates, internal regulations that mandate data updates only semiannually create an implementation gap. Theoretically, this study extends the digital public services literature by demonstrating that institutional constraints can limit the full potential of technology, not just technical factors or user resistance (Alshallaqi, 2024). Practically, these results emphasize the importance of synchronizing data update frequency with system capabilities and cross-sector needs so that SiPP can support more responsive social and employment interventions.